Distally Based Sural Artery Peroneus Flap (DBSPF) for Foot and Ankle Reconstruction - Ebrahiem, Ahmed Ali (Plast Reconstr Surg Glob Open, 2017)
BACKGROUND: Reconstruction of soft-tissue defects in lower third of leg, ankle, and foot has been a challenge and reconstructive surgeons have been trying to innovate different flaps. To solve this issue, we propose a distally based sural artery peroneus flap (DBSPF) in which we include superficial portion of the peroneus brevis muscle and its blood supply with the peroneal artery distally. The aim of this study was to evaluate the functional outcome and its usefulness over conventional distal sural artery flap or other local options available. METHODS: This is a case series of 20 patients that include a DBSPF that was done for defects around ankle, distal leg, and foot caused by trauma or tumor ablation within the period of June 2013 to March 2015 in Kasralainy Hospital, Cairo. All cases were evaluated according to flap vascularity, distal reach of flap, aesthetic outcome, and donor-site morbidity. RESULTS: All flaps survived. One flap developed venous congestion that subsided spontaneously with limb elevation. The flap dimension ranged from 42 cm to 442 cm(2), and it reached the midfoot easily. The pivot point was kept as low as 2–6 cm from lateral malleolus according to location of perforators. The ankle stability was maintained, and the desired aesthetic outcome was achieved. CONCLUSIONS: The DBSPF is an addition to the armamentarium in plastic surgery for defects around ankle, distal leg, and foot. It is an easy and swift procedure as compared with complex microsurgical reconstruction.